Increasing Product Promotion by Implementing Association Rules in The Web-Based Second_Oldshoes Store Sales System - Wulandari, Maria Sri; Noveandini, Rahayu; Dahlan, Fuadi Ahmad (International Journal Software Engineering and Computer Science (IJSECS), 2023)
Promotion is one of the efforts that can be made to maximize profits. Currently, there are various techniques and models for promoting products, both through social media and advertising systems. To get optimal promotional results, it is necessary to calculate the level of customer attraction to a product being offered. The second_oldshoes shop is an original second-hand shoe shop, currently the second_oldshoes shop does not have media to promote its products. The application of association rules in the system is used to display the associative value of each product that a customer buys so that a pattern is formed of the products that are often purchased by each customer. So, it can be used as a basis for decisions in determining suitable products to promote to each customer. The design of this web-based sales system uses Navigation Structure and Unified Modeling Language (UML). Creating a system using the HTML, PHP, CSS, JavaScript, MySQL, and Bootstrap programming languages as a framework.